Physiological responses of Brazilian amphibians to an enzootic infection of the chytrid fungus Batrachochytrium dendrobatidis - Bovo, Rafael P. [UNESP]; Andrade, Denis V. [UNESP]; Toledo, Luis Felipe; Longo, Ana V.; Rodriguez, David; Haddad, Celio F. B. [UNESP]; Zamudio, Kelly R.; Guilherme Becker, C. [UNESP] (Inter-research, 2016)
Pathophysiological effects of clinical chytridiomycosis in amphibians include disorders of cutaneous osmoregulation and disruption of the ability to rehydrate, which can lead to decreased host fitness or mortality. Less attention has been given to physiological responses of hosts where enzootic infections of Batrachochytrium dendrobatidis (Bd) do not cause apparent population declines in the wild. Here, we experimentally tested whether an enzootic strain of Bd causes significant mortality and alters host water balance (evaporative water loss, EWL; skin resistance, R-s; and water uptake, WU) in individuals of 3 Brazilian amphibian species (Dendropsophus minutus, n = 19; Ischnocnema parva, n = 17; Brachycephalus pitanga, n = 15). Infections with enzootic Bd caused no significant mortality, but we found an increase in Rs in 1 host species concomitant with a reduction in EWL. These results suggest that enzootic Bd infections can indeed cause sub-lethal effects that could lead to reduction of host fitness in Brazilian frogs and that these effects vary among species. Thus, our findings underscore the need for further assessment of physiological responses to Bd infections in different host species, even in cases of sub-clinical chytridiomycosis and long-term enzootic infections in natural populations.
Keywords: Chytridiomycosis; Amphibian declines; Fitness; Evaporative water loss; Water uptake; Amphibian skin; Mortality